Three‐dimensional speckle tracking echocardiography to evaluate left ventricular function in patients with acute ST‐segment elevation myocardial infarction after percutaneous coronary intervention following Tongxinluo treatment. Issue 9 (31st August 2022) - Qin, Wenjuan; Tian, Ruimeng; Feng, Jia; Zhai, Zijing; Wang, Zhen; Huang, Lei; Lu, Guilin; Dong, Shanshan
Abstract: Objective: Bying comparing the correlation between three‐dimensional speckle tracking echocardiography (3D‐STE) and troponin I (cTn I), three‐dimensional left ventricular ejection fraction (3D‐LVEF), to explore the 3D‐STE to evaluate the left ventricle of patients with acute ST‐segment elevation myocardial infarction (AMI) after percutaneous coronary intervention (PCI) following routine treatment with Tongxinluo drugs. Methods: Altogether, 61 patients with AMI and 30 healthy adults were selected, and the patients were divided into the routine group and the Tongxinluo group. The serum creatine kinase isoenzyme (CK‐MB) and troponin I (cTn I) levels were detected in all patients after admission. All patients underwent PCI, and routine echocardiography and 3D‐STE assessments were performed for each group 72 h after PCI and 12 months after PCI to obtain the following left ventricular‐related functional parameters: left ventricular end‐diastolic diameter (LVEDD), end‐ventricular septal end‐diastolic thickness (IVSD), left ventricular posterior wall end‐diastolic thickness (LVPWD), left ventricular short axis shortening fraction (LVFS), Simpson's left ventricular ejection fraction (Simpson's LVEF), three‐dimensional left ventricular ejection fraction (3D‐LVEF), global longitudinal strain (GLS), global circumferential strain (GCS), left ventricular twist angle (LVtw), Torsion (Tor), peak strain dispersion (PSD), and myocardial comprehensive index (MCI). The same parameters were collected in the control group, the results were compared. The correlation analysis between 3D‐STE parameters and 3D‐LVE, cTn I was performed. A total of 10 individuals were selected for repeatability testing. Results: Compared with the control group, the LVFS, LVEF (Simpson), 3D‐LVEF, GLS, GCS, LVtw, Tor, and MCI significantly decreased in patients with STEMI after PCI, while the PSD significantly increased ( p  < 0.05). Compared with the values 72 h after PCI, the LVEDD, LVFS, LVEF (Simpson), 3D‐LVEF, GLS, GCS, LVtw, Tor, and MCI significantly increased at 12 m after PCI, while PSD significantly decreased ( p  < 0.05). No significant difference was observed between the two groups at 72 h after PCI ( p  > 0.05). At 12 months after PCI, the LVEF, GLS, GCS, LVtw, Tor, and MCI of the Tongxinluo group were higher than those of the routine group. The PSD was significantly lower in the Tongxinluo group ( p  < 0.05). MCI and 3D‐LVEF, cTn I have the strongest correlation and the highest consistency, which can best reflect the changes in the left ventricular function in patients with AMI after PCI. Conclusion: 3D‐STE can be used to evaluate the protective effect of Tongxinluo on the left ventricular function in patients with AMI after PCI. Abstract : Bying comparing the correlation between three‐dimensional speckle tracking echocardiography (3D‐STE) and troponin I (cTn I), three‐dimensional left ventricular ejection fraction (3D‐LVEF), to explore the 3D‐STE to evaluate the left ventricle of patients with acute ST‐segment elevation myocardial infarction (acute STEMI) after percutaneous coronary intervention (PCI) following routine treatment with Tongxinluo drugs.